Control of the borer of the pineapple fruit (Thecla basilides, Geyer) with chlorate and phosphorate insecticides and carbamate - Zunti, Adauto C.; Cardinali, Lúcio R. (Pesquisa Agropecuaria Brasileira, 2014)
Control studies of pineapple fruit borer (Thecla basilides, Geyer) using chlorate insecticides, phosphorate and carbamate were carried out in Vespasiano and Pedro Leopoldo areas, Minas Gerais, Brazil. Between the different treatments there were (1) significant differences in the number of healthy fruit, (2) no significant differences in the kg/ha produced. Among the insecticides applied in liquid form, the “Carbaryl” 0.20 a.p. Naphthyl-n-methylcarbamate was the most efficient. As dusts, "Endrin" (0.10 a.p. Hexachloro-epoxy-octahydro-endo-endodimethanonaphtalene) and "Carbaryl" were the most promising.